2015
DOI: 10.1589/jpts.27.27
|View full text |Cite
|
Sign up to set email alerts
|

The effects of whirlpool bath and neuromuscular electrical stimulation on complex regional pain syndrome

Abstract: [Purpose] The aim of the present study was to investigate and compare the effects of whirlpool bath and neuromuscular electrical stimulation on complex regional pain syndrome. [Subjects and Methods] Sixty outpatients (30 per group) with complex regional pain syndrome participated. They received 15 treatment 5 days per week for 3 weeks. The outcome measures were the visual analogue scale for pain, edema, range of motion of the wrist (flexion and extension), fingertip-to-distal palmar crease distance, hand grip … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 23 publications
0
17
0
1
Order By: Relevance
“…Upper limb oedema. Similar to the results of studies assessing NMES for reducing lower limb oedema, there are 2 studies that support the feasibility and effectiveness of NMES for reducing upper limb oedema (16)(17). Other benefits found were improvements in pain, function, range of motion and strength.…”
Section: Study Limitationsmentioning
confidence: 64%
See 4 more Smart Citations
“…Upper limb oedema. Similar to the results of studies assessing NMES for reducing lower limb oedema, there are 2 studies that support the feasibility and effectiveness of NMES for reducing upper limb oedema (16)(17). Other benefits found were improvements in pain, function, range of motion and strength.…”
Section: Study Limitationsmentioning
confidence: 64%
“…1 and a summary of the studies sourced is shown in Table III. Seven studies assessed the role of NMES for reducing oedema (11)(12)(13)(14)(15)(16)(17). Oedema size, or swelling, was a primary outcome measure in all the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations